KENDALA DAN STRATEGI PENGUATAN MANAJEMEN PERPUSTAKAAN, AKSES INFORMASI MASYARAKAT - Lahagu, Rustam; Sitanggang, Parlindungan (Jurnal Manajemen, Ekonomi dan Akutansi (JUMEA), 2025)
Libraries are institutions that play a vital role in facilitating access to information, knowledge, and public literacy. The aim of this study is to determine the functions of management implemented by the Nias Regency Service of Library and Archives, to identify internal and external factors that influence the performance of management functions in increasing reading interest, and to determine the effectiveness of the implementation of existing management functions in enhancing services related to reading interest in that library. The library management functions at the Nias Regency Service of Library and Archives demonstrate a variety of aspects, including an emphasis on reading activities and the participation of staff members as well as the community in information access. There are different focal points regarding collection management, covering a diverse range of reading materials and the organization of programs that foster collaboration and discussion related to reading materials. Limited funding and resources are major constraints in the development of the library’s collection as well as in updating technology to improve information accessibility. Enhancing library management functions to be more effective and strategic is crucial to improve the availability and access to relevant collections, and to strengthen reading interest and public participation in reading activities at the Nias Regency Service of Library and Archives